2016
DOI: 10.1063/1.4968542
|View full text |Cite
|
Sign up to set email alerts
|

Surface scattering controlled heat conduction in semiconductor thin films

Abstract: Phonon-surface scattering is the fundamental mechanism behind thermal transport phenomena at the nanoscale. Despite its significance, typical approaches to describe the interaction of phonons with surfaces do not consider all relevant physical quantities involved in the phonon-surface interaction, namely, phonon momentum, incident angle, surface roughness, and correlation length. Here, we predict thermal conduction properties of thin films by considering an accurate description of phonon-surface scattering eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 54 publications
6
29
1
Order By: Relevance
“…It is also observed that the larger the cladding thickness, the larger the increase in the thermal conductivity of the germanium thin film. This is because, for larger thicknesses of the silicon cladding layers, phonon scattering at the interfaces is reduced 31 36 and silicon phonon mean free paths are not shortened previously to their injection in germanium. Note that the enhancement of conductivity via injection of phonons is not unbounded with increasing cladding thickness, rather it begins to saturate as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also observed that the larger the cladding thickness, the larger the increase in the thermal conductivity of the germanium thin film. This is because, for larger thicknesses of the silicon cladding layers, phonon scattering at the interfaces is reduced 31 36 and silicon phonon mean free paths are not shortened previously to their injection in germanium. Note that the enhancement of conductivity via injection of phonons is not unbounded with increasing cladding thickness, rather it begins to saturate as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…root-mean-square roughness and correlation lengths) between the cladding and internal layer. At the outer surfaces, the distribution function g k for a phonon leaving the surface is equal to the distribution function for the phonon striking the surface multiplied by the probability of specular surface scattering p ( k , θ , η , L ) where θ is the incident angle, η is the surface roughness and L is the correlation length 36 . On the other hand, at the silicon/germanium interface, the distribution function contains contributions from reflection and transmission events with probabilities P ( k , θ , η , L ) and Q ( k , θ , η , L ), respectively 38 .…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In thin two-dimensional structures, phonons experience additional scattering on the top and bottom surfaces [8][9][10]. Such surface scattering events should limit the phonon MFP in membranes as compared to bulk material [11], thus reducing the thermal conductivity and limiting the ballistic heat conduction. Indeed, the experimentally measured thermal conductivity of thin membranes are consistent with the MFP spectrum in bulk, assuming that the spectrum is limited by the membrane thickness [4].…”
Section: Introductionmentioning
confidence: 99%
“…We extend the electromagnetic wave scattering theory developed for rough surfaces by Beckmann and Spizzichino 36 to accurately model reflection and transmission at rough interfaces as well as phonon coupling between the layers by accounting for all the relevant physical variables such as phonon properties (e.g. momentum, incident angle) and surface characteristics (roughness, correlation lengths, and shadowing) 37 . By directly calculating the reduction in phonon relaxation times due to surface scattering through the rigorous solution of the Boltzmann transport equation, our analysis moves beyond the Mattheissen rule approximation for modelling surface scattering.…”
Section: Introductionmentioning
confidence: 99%